Systematic Literature Review: Profil Literasi Digital dalam Pembelajaran Biologi di Sekolah Menengah Atas - Yesi Desta Linda; Meita Dwi Solviana; Ovi Prasetya Winandari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The digital era demands that students be capable of accessing, comprehending, evaluating, and utilizing digital information critically and responsibly. However, studies specifically mapping digital literacy profiles within high school (SMA) biology education remain limited and fragmented. This study aims to identify research trends, describe primary research focuses, analyze students' digital literacy profiles, and map the benefits, challenges, and developments of research regarding digital literacy in high school biology education during the 2021–2025 period. The study employs a Systematic Literature Review (SLR) approach following the PRISMA protocol. Articles were retrieved using the *Publish or Perish* application, linked to Google Scholar and other reputable academic databases. Bibliometric analysis was conducted using VOSviewer software to map thematic interconnections and keyword trends. The findings indicate that the digital literacy profiles of high school students in biology education range from low to high, depending on the context and instruments employed. The most frequently studied digital literacy indicators include information-seeking skills, content evaluation, and digital navigation. Factors influencing digital literacy include technology availability, learning models, and the implementation of digital-based interactive media. The integration of digital platforms and media—such as e-modules, Google Classroom, Augmented Reality, and gamification-based media—has been shown to significantly enhance digital literacy. The study concludes that strengthening digital literacy in high school biology education requires a structured approach utilizing integrated, technology-based learning strategies.